Ecological Observations on the Grasslands of Corbett Tiger Reserve, India - Rawat, G. S.; Goyal, S. P.; Johnsingh, A. J. T. (Indian Forester, 1997)
Two grasslands (Chaurs) in the core area of Corbett Tiger Reserve were studied to compare the species composition, frequency and distribution of grasses, herbs and weeds. The studyrevealcd that less frequently burnt Chaurs of first site i.e. Dhikala had high frequency of weeds and tree saplings. On the other hand. the low lying wet grasslands showed a different species composition. The frequency of grasses was significantly lower in the areas of seasonal inundation compared to elevated grasslands of Dhikala Chaur (t = 2.899. p = <0.025). Since elevated and low lying grasslands represent different ecological conditions. these would require different management practices. Weeds in low lying wet areas can be eradicated by planting native tall grasses and weeds rather than attempts of burning.